USE OF APREPITANT AS AN ANTIEMETIC IN CYSTIC FIBROSIS PATIENTS. Issue 1 (1st March 2015) - Jamali, A; Harrison, M; Bilton, D; Simmonds, N; Ross, J
Abstract : Introduction: Aprepitant is a NK1 receptor antagonist licensed for treatment of nausea and vomiting (n&v) associated with emetogenic chemotherapy. There are case reports of use for n&v post-operatively or secondary to diabetic gastroparesis. There is no published evidence in patients with cystic fibrosis (CF). Tigecycline is used in treatment of Non-Tuberulosis Mycobacteria in CF. However uncontrolled n&v can result in dose reduction, interruption or discontinuation, and treatment failure. Aims: To evaluate the efficiacy and side-effects of aprepitant (added to domperidone and ondansetron) in CF patients requiring tigecycline treatment. Methods: Retrospective and prospective audits (studies) were conducted with case note review of consecutive CF patients receiving IV tigecycline, using a standardised proforma. Consecutive admissions for IV tigecycline therapy were consented and commenced on aprepitant 80mg OD for the first five days of tigecycline therapy. They completed daily n&v and side-effect diaries. Results: 16 case notes were evaluated retrospectively and 10 patients prospectively audited. Aprepitant was likely to have contributed to reduction in n&v in 17/26 (65%) cases. 9/10 (90%) patients in prospective audit completed the full course/dose of tigecycline. 8/26 (31%) cases reported mild side-effects (headache (3), hiccups, dyspepsia (2), abdominal pain, atrial tachycardia); all resolved on continuing aprepitant or persisted despite stopping aprepitant. Conclusion(s): Aprepitant was well tolerated and appeared to be effective for a number of CF patients. Ongoing work will further evaluate the benefit of aprepitant in this population and inform clinical guidelines for management of n&v in CF patients.